2021
DOI: 10.1093/scan/nsab028
|View full text |Cite
|
Sign up to set email alerts
|

The representation of mental state information in schizophrenia and first-degree relatives: a multivariate pattern analysis of fMRI data

Abstract: Individuals with a schizophrenia-spectrum disorder (SSD) and those at familial high-risk (FHR) for SSDs experience social difficulties that are related to neural abnormalities in the network of brain regions recruited during theory of mind (ToM). Prior work with these groups has focused almost exclusively on characterizing involvement of these regions in ToM. Here, we examine the representational content of these regions using multivariate pattern analysis. We analyzed two previously collected datasets of SSD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…In a study on student suicide risk prediction, Kumari et al used keywords extracted from text data published by microblog users for data analysis and used MLP models to achieve a predictive assessment of suicide risk based on microblog text data [8]. However, one of the obvious drawbacks of these studies is that they only focus on users who have social network accounts, such as Sina Weibo, and not every student uses Sina Weibo; in fact, according to the survey, the average number of active users of Sina Weibo is only 4 to 5 [9]. ere are no studies that show a psychological difference between Weibo users and non-Twitter users.…”
Section: Current Status Of Researchmentioning
confidence: 99%
“…In a study on student suicide risk prediction, Kumari et al used keywords extracted from text data published by microblog users for data analysis and used MLP models to achieve a predictive assessment of suicide risk based on microblog text data [8]. However, one of the obvious drawbacks of these studies is that they only focus on users who have social network accounts, such as Sina Weibo, and not every student uses Sina Weibo; in fact, according to the survey, the average number of active users of Sina Weibo is only 4 to 5 [9]. ere are no studies that show a psychological difference between Weibo users and non-Twitter users.…”
Section: Current Status Of Researchmentioning
confidence: 99%
“…The significant network found in our study extended from the OFC into the dmPFC, a region associated with social processes [35]. Dodell-Feder et al [36] found that psychotic patients showed reduced recruitment of the dmPFC during mental state interpretation, while Vargas et al [37] found that dmPFC efficiency in the mentalizing network was compromised in the clinically at-risk sample for psychosis. Persecutory ideation may be the result of the breakdown of the cognitive control system on social processing and outcome prediction.…”
Section: Discussionmentioning
confidence: 59%
“…e serial operation merges all local features to form a new global representation [17]. e core idea of the pairwise additive operation, on the other hand, is to give more information to the feature map without adding additional parameters to the network.…”
Section: Deep Convolutional Neural Network Designmentioning
confidence: 99%
“…Since the network does not really learn the spatial distribution of human joints but only fits the training set with a huge number of parameters, the final model cannot be applied to the actual scene. The serial operation merges all local features to form a new global representation [ 17 ]. The core idea of the pairwise additive operation, on the other hand, is to give more information to the feature map without adding additional parameters to the network.…”
Section: Deep Convolutional Neural Network Intelligent Analysis Of Sp...mentioning
confidence: 99%